1986
DOI: 10.1159/000238435
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Anticancer Agent Cisplatin in the Treatment of Human Cervical Squamous Carcinoma Xenografted in Nude Mice

Abstract: Two human squamous carcinomas of the cervix, established by serial passage in nude mice, are described. The reponse of the tumours to cis-diamminedichloro-platinum (CDDP) was assessed by comparing tumour weights and by histological observations. Tumours treated with CDDP 10 mg/kg/week for 2 weeks regressed significantly and microscopy revealed extensive degeneration. Treatment with CDDP 5 mg/kg/week produced tumour growth retardation and microscopy showed some degenerative changes, however, viable cells, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In vitro studies in human cancer cell lines and clinical trials in several tumour types have suggested a doseresponse relationship for cisplatin (Pillay et al, 1986;Bruckner et al, 1984;Ozols et al, 1985;Ozols, 1989;Gandara et al, 1989;Forastiere et al, 1987). The application of high doses or frequent administration of lower doses of cisplatin is however, hampered by side effects such as severe nausea and vomiting, neurotoxicity and nephrotoxicity.…”
mentioning
confidence: 99%
“…In vitro studies in human cancer cell lines and clinical trials in several tumour types have suggested a doseresponse relationship for cisplatin (Pillay et al, 1986;Bruckner et al, 1984;Ozols et al, 1985;Ozols, 1989;Gandara et al, 1989;Forastiere et al, 1987). The application of high doses or frequent administration of lower doses of cisplatin is however, hampered by side effects such as severe nausea and vomiting, neurotoxicity and nephrotoxicity.…”
mentioning
confidence: 99%
“…One of the major discoveries in cancer therapy has been the use of platinum drugs [1][2][3][4][5][6][7][8][9][10]. Of these, cis-dichlorodiammineplatinum II (cisplatin) has proven to be active against a broad spectrum of tu mor systems [11][12][13][14], As a result of using animal models, analogs with improved antitumor activities and reduced toxicities relative to cis-dichlorodiammineplatinum 1 Supported by MBRS Grant No.…”
Section: Introductionmentioning
confidence: 99%